k-cordial labeling of fan and double fan - Modha, Mita; Kanani, Kailas (International Journal of Applied Mathematical Research, 2015)
We discuss here k-cordial labeling of fans. We prove that fans \(f_{n}\) are k-cordial for all k. We divide the proof of the result into two parts namely odd k and even k. Moreover we prove that double fans \(Df_{n}\) are k-cordial for all k and \(n=\frac{k+1}{2}\). The present authors are motivated by the research article entitled as 'A-cordial graphs' by A Hovey.Â